The effects of two differing techniques on the accuracy of reagent strip blood glucose testing - Christopher Stein (AOSIS, 2007)
The use of 70% isopropyl alcohol to prepare the site of skin puncture for reagent strip blood glucose testing has been reported to produce falsely elevated blood glucose levels. Opsomming Volgens 'n verslag het die gebruik van 70% isopropyl alkohol om die plek van velpunktuur vir reagensstrook bloedglukosetoetsing voor te berei valslikverhoogde bloedglukosevlakke geproduseer. *Please note: This is a reduced version of the abstract. Please refer to PDF for full text.